2021
DOI: 10.3390/polym13183129
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of ASTM E1922 for Measuring the Translaminar Fracture Toughness of Laminated Polymer Matrix Composite Materials

Abstract: The main objective of this work is to predict the exact value of the fracture toughness (KQ) of fiber-reinforced polymer (FRP). The drawback of the American Society for Testing Materials (ASTM) E1922 specimen is the lack of intact fibers behind the crack-tip as in the real case, i.e., through-thickness cracked (TTC) specimen. The novelty of this research is to overcome this deficiency by suggesting unprecedented cracked specimens, i.e., matrix cracked (MC) specimens. This MC exists in the matrix (epoxy) withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Likewise, the current trend of K eff in MC specimens is compatible with the trend of K IC in mode I, which was found by Ali et al [39] experimentally and El-Sagheer et al [34] numerically. Like the present study, they found that the MC specimens with short fiber produced higher fracture toughness.…”
Section: Real Fracture Toughness Of MC Frcsupporting
confidence: 87%
See 2 more Smart Citations
“…Likewise, the current trend of K eff in MC specimens is compatible with the trend of K IC in mode I, which was found by Ali et al [39] experimentally and El-Sagheer et al [34] numerically. Like the present study, they found that the MC specimens with short fiber produced higher fracture toughness.…”
Section: Real Fracture Toughness Of MC Frcsupporting
confidence: 87%
“…Unfortunately, such previous work was not only a waste of time and effort but also led the scientific research compass in this field in the wrong direction for solving such problems. The first attempt in the right direction for predicting the fracture toughness of fibrous composite materials was made by Salam and colleagues [34,[36][37][38][39]. Sallam and co-workers [36,39] successfully correlated the mode I fracture toughness of FRC using MC specimens, i.e., correlating a vectorial problem with a crack path independent of the initial crack length by scalar parameters such as Griffith's energy release rate..…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The elastic constants and Hashin’s damage model strength data of the different layers, according to their V f %, are shown in Table 4 and Table 5 , respectively, extracted analytically as was described in refs. [ 31 , 43 ]. CZM was used to simulate the adhesive layers.…”
Section: Finite Element Model For the Sp Testmentioning
confidence: 99%
“… E / E nn = K 1 = ( E × α )/ t G 1 / E ss = K 2 = ( G 12 × α )/ t G 2 / E tt = K 3 = ( G 13 × α )/ t where E is the epoxy’s modulus of elasticity, G is the Shear modulus of epoxy, α is a constant = 50, and t = cohesive layer thickness. For more details, refer to Sec-1 : Mechanical properties of glass fiber-epoxy lamina; Sec-2 : Hashin Model Constants; Sec-3 : Hashin Damage Criteria; Computer Code : Computer Code.inp (see Supplementary Materials ) [ 31 , 40 , 43 , 45 ].…”
Section: Finite Element Model For the Sp Testmentioning
confidence: 99%